Litigantes habituais: análise discursiva dos pré- construídos enriquecimento ilícito e indústria do dano moral pelo Judiciário - Silva, Patrícia Cordeiro da (2024)
This work focuses on the discursive analysis of the use of the pre-constructed unjust enrichment and industry of moral damages against consumers by the judiciary, in judgments that recognize the violation of their rights by habitual litigants (predominantly large companies that move the largest part of the processes in the country), but deny the grant of moral damages, under the argument that it would cause unjust enrichment of the consumer and foster an industry of moral damages. For the constitution of the research corpus, 10 judgments of the São Paulo State Courts were collected, which deal with undue charges by habitual litigants against consumers, in cases in which it is recognized by the Court that the act practiced by the company was unlawful, but compensation for moral damages is not granted, being used the pre-constructed unjust enrichment or industry of moral damages as arguments for the non-grant. The São Paulo State Court was chosen considering that it is the state with the largest number of lawsuits in Brazil. Additional materials were also used, such as research on litigation in Brazil, produced by the Brazilian Association of Magistrates, in which the reasons why judges believe that there are more lawsuits are presented, as well as research by the CNJ (National Council of Justice) on the largest litigants in the country. The corpus was analyzed based on French-oriented Discourse Analysis. The research had the following specific objectives: a) to analyze how the functioning of legal discourse occurs; b) to discuss how the productivity goals of judges can influence the continued use of the pre-constructed unjust enrichment and industry of moral damages against the consumer; c) to discuss which are the erasures and silences produced by these effects of meaning. Analyzing the corpus it was possible to observe that although the judgments recognize that the consumer was harmed, that is, that his right was violated, moral damages are not recognized on the grounds that he allegedly suffered only a mere annoyance, instituting another parameter that is not a legal parameter of what would be a type of annoyance compensable or not by the judiciary and erasing the situations of the specific case.